Population dynamics of an experimental plot of biodiversity and ecosystem functioning in the Pingshuo open-pit mine - Ren, Hong (Frontiers in Ecology and Evolution, 2025)
This study evaluates the decadal population dynamics of vegetation restoration in a 2.8 hm² biodiversity-ecosystem functioning plot within Pingshuo open-pit mine’s reclamation area, comparing 2013 and 2023 survey data. This decade-long study focuses on survival dynamics, growth patterns, and interspecific interactions among four pioneer species: locust, oil pine, sea buckthorn, and Caragana microphylla. Through experimental plots with diverse planting configurations, mixed models revealed critical trade-offs between facilitation and competition. Oil pine and locust exhibited mutually beneficial interactions, achieving near-complete survival in paired configurations, while combinations involving sea buckthorn and caragana microphylla suffered marked competitive suppression. Monoculture outcomes varied. Locust thrived independently, whereas oil pine showed enhanced survival in mixed communities. Morphological traits displayed configuration-dependent plasticity, with locust-sea buckthorn combinations optimizing growth across species, and oil pine demonstrating superior basal development in isolation. Notably, shrub vulnerability to niche overlap contrasted with tree resilience, suggesting divergent adaptive strategies in moisture-limited environments. The study highlights the importance of species compatibility, functional trait complementarity, and phased planting approaches to balance competitive dynamics. Key findings propose the locust-sea buckthorn configuration as a strategic model for promoting multi-species growth, offering actionable insights for ecological restoration in degraded post-mining landscapes.